2017
DOI: 10.3390/nu9030232
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Insomnia Symptoms in Chinese Adults: The China Kadoorie Biobank

Abstract: Limited attention has been paid to the effect of dietary patterns on sleep problems. In the present study, we analyzed the cross-sectional data of 481,242 adults aged 30–79 years from the China Kadoorie Biobank. A laptop-based questionnaire was administered to collect information on food intakes and insomnia symptoms. Logistic regression was used to estimate the odds ratios of each insomnia symptom according to quartiles of each dietary pattern, with adjustment for potential confounders. Two major dietary patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 39 publications
2
39
0
1
Order By: Relevance
“…Fruits consumption was likewise found to be positively related to sleep duration (Gong et al, ; Haghighatdoost et al, ). The findings that higher adherence to Mediterranean diet (Campanini et al, ) or Chinese modern dietary patterns (Yu et al, ), both of which are characterized by high intake of fruits and other specific foods, were associated with better sleep quality strengthen our result. Furthermore, a review implied fruits may promote sleep duration and efficiency (Peuhkuri, Sihvola, & Korpela, ).…”
Section: Discussionsupporting
confidence: 79%
“…Fruits consumption was likewise found to be positively related to sleep duration (Gong et al, ; Haghighatdoost et al, ). The findings that higher adherence to Mediterranean diet (Campanini et al, ) or Chinese modern dietary patterns (Yu et al, ), both of which are characterized by high intake of fruits and other specific foods, were associated with better sleep quality strengthen our result. Furthermore, a review implied fruits may promote sleep duration and efficiency (Peuhkuri, Sihvola, & Korpela, ).…”
Section: Discussionsupporting
confidence: 79%
“…However, this method of fracture reporting has been used in a previous study [ 34 ] and in China the highest incidence rates of fracture occurred on tibia and fibula (0.76 fractures per 1000 people) and radius and ulna (0.63 per 1000 people) [ 48 ]. Thirdly, although we adjusted for potential confounders, residual confounding from unmeasured lifestyle variables (such as from duration of sleep [ 48 , 51 ]) is still possible. In addition, not being able to adjust for medication (such as psychoactive medications) and supplement (hormonal and dietary) use could potentially overestimate the associations.…”
Section: Discussionmentioning
confidence: 99%
“…From Table A1, we can see that participants in this pattern followed a diet dominated by plant foods. In other studies deriving patterns from food consumption data, this pattern has often been referred to as the ‘traditional northern pattern’ . Participants in the CAF pattern had more animal fat and carbohydrate, because they consumed more animal oil and cereals than others.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies deriving patterns from food consumption data, this pattern has often been referred to as the 'traditional northern pattern'. 24,28 Participants in the CAF pattern had more animal fat and carbohydrate, because they consumed more animal oil and cereals than others. Previous studies suggested that nutrient patterns that were rich in carbohydrate and fat were associated with obesity 29 and might increase the risk of fractures.…”
Section: Discussionmentioning
confidence: 99%